2023
DOI: 10.1200/jco.22.02392
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Endocrine Therapy With or Without Ribociclib After Progression on Cyclin-Dependent Kinase 4/6 Inhibition in Hormone Receptor–Positive, Human Epidermal Growth Factor Receptor 2–Negative Metastatic Breast Cancer: MAINTAIN Trial

Abstract: PURPOSE Cyclin-dependent kinase 4/6 inhibitor (CDK4/6i) with endocrine therapy (ET) improves progression-free survival (PFS) and overall survival (OS) in hormone receptor–positive (HR+), human epidermal growth factor receptor 2–negative (HER2–) metastatic breast cancer (MBC). Although preclinical and clinical data demonstrate a benefit in changing ET and continuing a CDK4/6i at progression, no randomized prospective trials have evaluated this approach. METHODS In this investigator-initiated, phase II, double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 31 publications
(39 reference statements)
0
39
0
2
Order By: Relevance
“…However, MAINTAIN trial offered the initial evidence that using ribociclib and switching ET had significantly improved the median PFS compared to placebo plus switching ET after progression on a prior CDK4/6 inhibitor (86.5% palbociclib) (5.29 months vs. 2.76 months). 39 Whereas, continuing palbociclib plus switching ET after progression on palbociclib did not show clinical benefit in the phase II PACE trial 40 and PALMIRA trial. 41 These inconsistent findings imply that the rechallenge strategy of CDK4/6 inhibitors might not be suitable for all CDK4/6 inhibitors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, MAINTAIN trial offered the initial evidence that using ribociclib and switching ET had significantly improved the median PFS compared to placebo plus switching ET after progression on a prior CDK4/6 inhibitor (86.5% palbociclib) (5.29 months vs. 2.76 months). 39 Whereas, continuing palbociclib plus switching ET after progression on palbociclib did not show clinical benefit in the phase II PACE trial 40 and PALMIRA trial. 41 These inconsistent findings imply that the rechallenge strategy of CDK4/6 inhibitors might not be suitable for all CDK4/6 inhibitors.…”
Section: Discussionmentioning
confidence: 98%
“…To date, three randomized phase II trials have been reported to evaluate this approach. 39 , 40 , 41 Only the MAINTAIN trial demonstrated positive results, 39 whereas the PACE trial and PALMIRA trial showed negative results. 40 , 41 Therefore, more data are needed to determine the sequence and principle of reuse of CDK4/6 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…From the German perspective, "TbP" might be an option due to side effects. In the MAINTAIN trial [11], CDK4/6 inhibitor plus switching endocrine monotherapy was superior to endocrine monotherapy and showed a benefit in median PFS (HR 0.57; p = 0.006). The German experts also point to the numerous treatment alternatives after ET-based first-line therapy such as elacestrant in case of ESR1 mutation, alpelisib/fulvestrant for patients with PIK3CA mutation, as well as everolimus plus ET or fulvestrant as monotherapy [1].…”
Section: Maintenance Therapy After First-line Chemotherapymentioning
confidence: 99%
“…The MAINTAIN trial demonstrated a significant progression-free survival (PFS) benefit for patients with HR + /HER2 – MBC who switched ET and received ribociclib compared with placebo after previous CDK4/6i. In contrast, the PACE trial revealed no evident PFS advantage, whereas the PALMIRA trial illustrated that maintaining a regimen of palbociclib alongside endocrine therapy did not yield superior PFS outcomes compared to endocrine therapy alone ( 7 - 9 ).…”
mentioning
confidence: 91%